Flujo de genes entre frijol comun silvestre en Costa Rica - Chaves Barrantes, N.=700 1 Araya Villalobos, R.; Debouck, D.
(Es, En)
Ilus., 23 ref.
Keywords: PHASEOLUS VULGARIS; ALOGAMIA; HIBRIDACION; APIDAE; BOMBUS; COSTA RICA; FRIJOL SILVESTRE; AGRONOMIA MESOAMERICANA